Paid to quit - Robert Dur; Heiner Schmittdiel (Tinbergen Institute, 2013)
Inspired by a recent observation about an online retail company, this paper explains why a firm may find it optimal to offer an exit bonus to recent hires so as to induce self-selection. We study a double adverse selection problem, in which the principal can neither observe agents' commitment to the job nor their intrinsic motivation. A steep wage-tenure profile deters uncommitted agents from applying. An exit bonus can stimulate that –among the committed agents– those who discovered that they are not intrinsically motivated for the job discontinue employment with the principal. Our key findings are that offering an exit bonus increases profits when the first adverse selection problem is sufficiently severe compared to the second and that the exit bonus needs to come as a surprise for the agents in order to function well.
Keywords: J31; J33; M52; M55; 330; intrinsic motivation; commitment; self-selection; wage compensation; exit bonus; transparency